IMPACTS OF MEDIA LITERACY LEVELS ON HUMAN TRAFFICKING (TPPO) CONTENT - Popi Andiyansari; Ade Irma Sukmawati (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
New media is rapidly evolving and has an impact on our daily life. The rapid development of applications and increasing number of social media users can lead the users in a vulnerable condition. Human trafficking, also known as TPPO (Tindak Pidana Perdagangan Orang) in Indonesia, is one of the threats that users encounter, it commonly happens to young users who do not have enough information about it, but they can obtain TPPO information through employment advertisements in the media. The goal of this study is to look at media literacy levels and the correlations between them and TPPO message comprehension in new media. This research used a descriptive quantitative method with a correlation approach, in which associations between variables were measured. The media literacy levels of respondents were measured by using a Likert scale with a range of 1-5. The aspects measured were age, school origin and ownership of social media. These aspects and the TPPO message understanding in new media were measured by a Pearson scale. This study found that the highest level of media literacy was in the age group of 15 years old from SMAN 1(Public Senior High School) Pakem and that the number of social media account ownership did not show a significant relationship with the literacy levels. The measurement on the relationships between the media literacy levels and the TPPO message understanding by using a Pearson scale obtained 0.606; these results indicated that the correlation between both variables was high.